2022
DOI: 10.3389/fbioe.2022.1078626
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of manure for mineral P fertilizers increases P availability by enhancing microbial potential for organic P mineralization in greenhouse soil

Abstract: The shortage of phosphorus (P) as a resource represents a major challenge for the sustainable development of agriculture. Manure has a high P content and is a potential substitute for mineral P fertilizers. However, little is known about the effects on soil P availability and soil microbial P transformation of substituting manure for mineral P fertilizers. In this study, variations in soil P availability and bacterial P mobilization were evaluated under treatment with manure as compared to mineral P fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, the relatively short duration of our greenhouse experiment compared to field conditions in which maize and soybean would be grown beyond the vegetative stage to grain harvest would be expected to underestimate the total amount of mineralization of phytin-P relative given the longer timescales of a growing season. On the other hand, the sustained warm (30˚C) and wet (40% soil water holding capacity) conditions of our greenhouse experiment would be expected to favor mineralization (Sun et al, 2022), especially given the temperature optimum of soil bacterial and fungal phytases of 20-40˚C (Azeem et al, 2015). Another potential contributing factor could be the relative abundance of phytate-mineralizing microbial species, which can differ in phytase isozymes and thus catalytic efficiency across soils (Singh & Satyanarayana, 2011).…”
Section: Mechanisms Of Phosphatase-driven Mineralization Of Phytate-pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relatively short duration of our greenhouse experiment compared to field conditions in which maize and soybean would be grown beyond the vegetative stage to grain harvest would be expected to underestimate the total amount of mineralization of phytin-P relative given the longer timescales of a growing season. On the other hand, the sustained warm (30˚C) and wet (40% soil water holding capacity) conditions of our greenhouse experiment would be expected to favor mineralization (Sun et al, 2022), especially given the temperature optimum of soil bacterial and fungal phytases of 20-40˚C (Azeem et al, 2015). Another potential contributing factor could be the relative abundance of phytate-mineralizing microbial species, which can differ in phytase isozymes and thus catalytic efficiency across soils (Singh & Satyanarayana, 2011).…”
Section: Mechanisms Of Phosphatase-driven Mineralization Of Phytate-pmentioning
confidence: 99%
“…We tested the hypothesized potential of phytin to partially substitute for conventional inorganic P fertilizers with high water solubility and evaluated potential mineralizationimmobilization mechanisms that dictate net availability of phytin-P. To this end, we assessed the vegetative growth response of maize and soybean, the two dominant crop species co-located in the region of high phytin production potential from ethanol plants of the US Midwest. In a greenhouse experiment, a phytin substitution gradient for MAP was applied in P-deficient Mollisol, a soil type representative of the US Midwest sub-regions with high crop productivity (Sun et al, 2022). Across the phytin substitution gradient (0%-100% phytin at 25% intervals), our objectives were to (1) quantify maize and soybean aboveground biomass, P uptake, and apparent PUE and (2) test hypothesized mechanisms of phosphatase-driven mineralization of phytate-P and assess microbial biomass C versus P limitation (i.e., immobilization) that would explain crop response to increasing phytin substitution for MAP.…”
Section: Core Ideasmentioning
confidence: 99%
“…It contains a high amount of nitrogen (N), phosphorus (P), potassium (K), and micronutrient elements. Thus, it is a potential substitute for chemical fertilizers (Sun et al, 2022a), and studies have found that straw returning efficiently improved soil structures and increased soil nutrient levels and crop yield (Sun et al, 2015;Chen et al, 2017Chen et al, , 2022. However, the direct straw return may also result in environmental and production risks in agricultural systems, such as stimulating CH 4 emission and aggravating plant pest infestation (Li et al, 2018;Kerdraon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with chemical fertilizers, manure is considered a friendlier substrate for soil microbial ecology, as many studies have shown that manure is more beneficial to the stabilization of soil microbial assemblages ( Sun et al, 2015a , 2023b ); thus, using manure to substitute mineral fertilizers may also be conducive to improving soil microbial diversity and ecological functions. Our recent study showed that the substitution of manure for mineral P fertilizers significantly increased soil P availability and enhanced microbial organic P mineralization capacity ( Sun et al, 2022a ). The results confirmed the feasibility of applying manure instead of mineral P fertilizers in greenhouse farming.…”
Section: Introductionmentioning
confidence: 99%